The concept of creating a pulse water gun with a large action range - Tolkachev, Anatoly; Sydorenko, Iryna; Morozov, Ihor (Eastern-European Journal of Enterprise Technologies, 2018)
We presented the concept of creation of a pneumatic pulse water gun. Its original feature is a use of a developed turbulent flow at the attenuation stage for formation of a jet. We suppose to create the required structure of small-scale turbulence according to a known procedure by means of a lattice in a barrel channel. The maximum intensity of this turbulence will be at a certain distance from a lattice, where a nozzle must be installed to take a turbulent structure into a jet. Well-known theoretical concepts and experimental facts give possibility to state that small-scale turbulence has the property of flow stability to excitations. We assumed that this property would act in a jet and provide its stability before expenditure of turbulence energy and prevent appearance of large-scale turbulence. Thus, it will delay the disintegration of a jet and increase a range of its flight. The analysis of a flow in known fountains with a transparent jet showed that representation of a laminar mode in them is incorrect. We presented a substantiation that special properties of jets are a consequence of a turbulent flow in fountains. This conclusion speaks in favor of the proposed use of turbulence as a tool against vortex formation. However, it is not possibly to apply the technique of creation of a jet in fountains for a high-power pulse water gun. We proposed a schematic diagram of the pulse water gun with a pneumatic ejection of a water projectile. An obvious problem of combination of a pulse flow with creation of small-scale turbulence is instability of a flow at the initial moment of a pulse. We showed the way of the solution to this problem by the experimental determination of real flow characteristics in a particular water gun design. We offered solutions to the most important technical issues of water gun creation.